Culturally competent engagement : a mindful approach - Brantmeier, Edward J.; Brantmeier, Noorie K. (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2020)
"Culturally Competent Engagement: A Mindful Approach embraces a fresh approach to cultivating self, other, and systems awareness for a linguistically rich and culturally diverse world. The confluence of people and cultures requires habits of mind, dispositions, skills, and values that promote diversity affirmation while simultaneously honoring one's own cultural integrity and limitations. The benefits of being culturally competent are numerous and include healthy, holistic relationships and connection with people across differences. This book provides conceptual context for tried and true learning exercises that promote deeper self-understanding, ways to connect with people who are culturally different, and an understanding of the systems (socio-cultural, economic, political, and environmental) that circumscribe our lives. Written for organizational leaders, university instructors, students, and pracitioners, this book includes typical approaches to enhancing culturally competent engagement, yet has several special features that differentiate it from approaches in other books and articles on the topic. Typical approaches to developing cultural competence focus on acquisition of communicative skills, behaviors, and dispositions needed to effectively navigate cross-cultural relationships and function effectively in multicultural environments. We include and build on these approaches by adding a layer of critical and complex systems understanding as a necessary foundation for effective cross-cultural engagement. The Self-Other-Systems approach challenges readers via concrete learning exercises that nudge one along the life-long path of culturally competent engagement. Perhaps the most unique feature of this book is the explicit and implicit mindful approach. A total of eleven learning exercises are offered, foregrounded by theory and completed with reflection questions or activities. All learning exercises encourage mindfulness, or awareness of oneself in the present moment, awareness of others, and awareness of broader contexts and forces at work in multicultural contexts. In specific, three learning exercises are meditations that can be read or listened to via free download from the book's website"-- Provided by publisher.
Keywords: Multicultural education -- United States.; Intercultural communication -- United States.; Cultural competence -- United States.; Education -- Professional Development.; Teacher training.; elektronické knihy; electronic books